2016
DOI: 10.1039/c5cy01341k
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of a self-assembled Pd(ferrocenylimine)–Si compound-catalysed Suzuki coupling reaction

Abstract: The Suzuki coupling reaction catalysed by a self-assembled monolayer of palladium(II) ferrocenylimine complex (Pd (FcL)-Si) was studied in detail. The precatalyst hybrid was used for the in situ reduction of the catalytically active Pd 0 to investigate the catalysis reaction using water-drop contact angle, atomic force microscopy, Raman spectroscopy, cyclic voltammetry and X-ray photoelectron spectroscopy. The first reaction step on the substrate, i.e., the oxidative addition of aryl halide to Pd 0 (FcL)-Si, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…In the modification process of substrates with catalyst, higher stability and superior activity of catalyst can be made by Self‐assembled monolayer method, with which a series of palladacycle imines was designed and utilized for catalyzing reaction, in which catalytic molecular monolayer exhibited efficient catalytic activity and recycling ability ,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the modification process of substrates with catalyst, higher stability and superior activity of catalyst can be made by Self‐assembled monolayer method, with which a series of palladacycle imines was designed and utilized for catalyzing reaction, in which catalytic molecular monolayer exhibited efficient catalytic activity and recycling ability ,…”
Section: Introductionmentioning
confidence: 99%
“…Molecular with double Schiff‐base moieties immobilized on GO were selected as the binding site, in which the C=N could present suitable steric, electronic and coordination, while the modified GO by organic molecules changes its electronic properties for tuning the activity and affecting the selectivity. Therefore, on the basis of researches,, graphene oxide with special properties is considered as support, aiming at designing the catalyst containing different metal ions having synergism between them, in which one molecular fixed on GO with double Schiff‐base groups as the binding site for different metal ions, such Pd and Ni which are in the same group . In this paper, we have been interested in the preparation of heterogeneous catalysts based on Schiff‐base transition bimetallic complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45] Previous studies showed that the activity of the bimetallic catalysts, or their monolayer and their recyclability, could be enhanced by tuning their orientation of the organometallic molecular, component, morphology and distributions of the active species, relating to the electrical characteristics of the supports, ligands, and synergism of the mono-or hetero-bimetallic catalytic lms. 4,16,35,37,39,44,[46][47][48][49][50][51][52][53][54][55] By now, multicomponent catalysts have made great progress, such as multi-metallic NPs, who have more variables available for tuning their catalytic activity. 56 Research on introducing a third or fourth metal to the ordered catalytic molecular monolayer is limited.…”
Section: Introductionmentioning
confidence: 99%
“…24 Previous studies have shown that the catalytic activity of the heterobimetallic catalysts could be enhanced by tuning their composition, morphology and the relative distributions of electrons, which are related to the electrical characteristics of the ligand, supports, and the synergy of hetero-bimetals. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Appropriate supports could promise a high dispersion of metallic catalyst and the maximum utilization of noble materials has attracted much attention; 19,40 graphene oxide (GO) has been recognized as an ideal candidate for supporting various metals and their complexes. [41][42][43] Pd catalyst doped with Ni, Fe, Co or Cu, reduces the loading of Pd and signicantly enhances catalytic activity by adjusting the distance between nickel and palladium, charge distribution and the arrangement of active sites.…”
Section: Introductionmentioning
confidence: 99%